A holistic review on Cryptococcus neoformans. (May 2022) - Rathore, Sudarshan Singh; Sathiyamoorthy, Jananishree; Lalitha, Cheepurupalli; Ramakrishnan, Jayapradha
Abstract: Cryptococcus neoformans is an encapsulated fungal pathogen that causes infection in immunocompromised individuals such as HIV patients, organ transplant patients, hematological malignancies, diabetes patients, etc. The most common invasive fungal pathogens are Candida spp., Aspergillus spp., and Cryptococcus spp. Cryptococcal meningitis has become increasingly common in immunocompromised patients resulting in a death rate of up to 90%. In low-income and middle-income countries, C. neoformans is a neglected killer in most parts of the world. It has unique and complicated virulence factors that facilitate its intracellular survival and dissemination. The initial infection, latency, or dissemination of the pathogen is determined by its specific morphological features such as capsule size, melanin pigment, biofilm development, etc. In this review, we discussed the worldwide distribution, classification of Cryptococcus spp., and a major focus on the pathogen's strategies that allow it to survive, proliferate subsequently disseminate resulting in cellular damage and treatment. Highlights: Emergence of diverse molecular types of Cryptococcus spp. is challenging to identify and devise treatment strategies for cryptococcosis. The capsular polysaccharide of C. neoformans protects itself from biological stress and immunomodulatory effects of the host. Crptococcus neoformans inhibits phagosomal maturation and leads to dissemination. Covid- 19 patients rarely gets coinfection of C. neoformans.